Diet Formulation Method Influences the Response to Increasing Net Energy for Growing-Finishing Pigs - D. Marcal; M. D. Tokach; S. S. Dritz; J. C. Woodworth; R. D. Goodband; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2016)
The objective of this study was to compare the effects of increasing dietary net energy (NE) in growing-finishing diets with maintaining a standardized ileal digestible (SID) Lys:NE ratio or not adjusting this ratio and keeping SID Lysine (Lys) constant across increasing NE density. A total of 150 pigs (Line 600 Duroc × Line 241, DNA, Columbus, NE) were used in a 91-d trial. Pens of pigs were blocked by gender and BW before being randomly assigned to treatments with 2 pigs per pen and 15 pens per treatment. Treatment diets included a low-energy negative control diet and a 2 × 2 factorial arrangement of treatments with main effects of increasing dietary NE (medium vs. high) and formulation method (constant SID Lys:NE ratio vs. constant percentage SID Lys). Increasing NE increased (linear, P = 0.001) daily NE intake and improved (linear, P<0.02) F/G with both formulation methods; however, ADG and HCW only increased (linear, P<0.03) when a constant SID Lys:NE ratio was maintained as dietary NE increased. These results demonstrate the importance of maintaining a constant Lys:NE ratio when changing the NE of the diet for growing pigs.
Keywords: calorie:lysine ratio; growing-finishing pig; lysine; net energy